Comparison of Reading Skills Between Children who Attended and those who did not Attend Early Childhood Education - Suhayyatman (Saniya Institute, 2025)
This research investigates the impact of early childhood education on first-grade primary school students' early reading abilities in Bagik Payung Timur Village, Suralaga District, East Lombok Regency, West Nusa Tenggara Province. A comparative approach examined differences between 33 children enrolled in early education programs and 33 non-enrolled peers, utilizing a census sampling method across the total population of 66 first-graders. Reading proficiency was assessed via standardized tests, analyzed through descriptive statistics and independent t-tests employing SPSS software (version 22). Findings revealed significant disparities: participants in early education averaged 118.09 out of 150 on reading assessments, compared to merely 17.36 among non-participants. Inferential testing confirmed statistical significance (p < 0.05), rejecting the null hypothesis and affirming superior reading outcomes for those exposed to preschool programs. These insights underscore early education's pivotal role in foundational literacy development.